A política da tolerância e o reconhecimento da diferença - Gondim, Larissa Cristine Daniel (2011)
There are many possible meanings for the word toleration, however, in this research, what is intended to analyze is a specific perspective of political toleration, that is, the toleration as recognition. The toleration as recognition is grounded in an type of political theory that, beginning with a criticism of the liberal tradition of toleration, in this research represented by the work of John Locke, Stuart Mill and John Rawls, tries to approximate the theories of toleration with the theories of recognition, in their turn represented by Charles Taylor, Axel Honneth, Nancy Fraser and Anna Elisabetta Galeotti. From this theoretical paradigm, it is intended to promote a complementation of the liberal tradition of tolerance, in a way to make it more inclusive. Recognize to tolerate begins to mean a positive action of reflexive understanding between individuals with divergent and conflicting conceptions of the good, that begins to self perceive themselves as subjects of reciprocal rights. This reformulation of the concept of toleration tends to be more efficient in the sense that is deals in a better way with the problems brought by multiculturalism in the democratic contemporary societies. In the end, it is concluded that this new meaning of tolerance is not only possible, but also changes itself into an instrument of social and political justice.